Arab Republic of Egypt - Cost of Environmental Degradation : Air and Water Pollution - Larsen, Bjorn (World Bank, Washington, DC, 2019)
Quantitative assessments of health impacts from environmental pollution are useful informationfor government and the general public. Such assessments can serve as an instrument to identify environmental priorities, mobilize support for their implementation, and, more broadly, to advance toward realizing environmental objectives. This report provides estimates of health effects of ambient air pollution (AAP) in Greater Cairo, and inadequate household drinking water, sanitation, and hygiene (WASH) nationwide in Egypt. Monetized estimates are provided of the social and economic cost of these health effects in Egyptian pounds and as a percentage of Egypt’s Gross Domestic Product (GDP) in 2016/17, using standard economic valuation techniques. The report finds that 19,200 people died prematurely and over 3 billion days were lived with illness in Egypt in 2017 as a result of ambient PM2.5 air pollution in Greater Cairo, and inadequate water, sanitation, and hygiene in all of Egypt. The estimated cost of these health effects was equivalent to 2.5 percent of Egypt’s GDP in 2016/17. The cost of ambient PM2.5 air pollution in Greater Cairo was highest, with a central estimate of LE 47 billion, equivalent to 1.35 percent of GDP. The cost of inadequate drinking water, sanitation, and hygiene nationwide was LE 39 billion, equivalent to 1.15 percent of GDP. However, water related costs are likely higher than suggested by this figure because of undetermined exposure to lead, other heavy metals, and chemicals through drinking water. On a per capita basis, the cost of ambient air pollution in Greater Cairo was LE 2.7 billion per one million people. This is nearly seven times higher than the nationwide cost per million people of inadequate water, sanitation, and hygiene. While the report finds that air quality, in terms of PM2.5 concentrations, improved in Greater Cairo over the period from 1999 to 2016, it was outpaced by population growth, resulting in an increase in annual deaths from ambient PM2.5. Annual deaths from ambient PM2.5 per 100,000 people did, however, decline by 8 percent from 79 to 73 from 1999 to 2017.